A study on the impact of enterprise digital transformation on informed trading. - Hualing Wang (PLoS ONE)
Informed trading, driven by information asymmetry and market imperfections, varies in presence across markets. This form of trading not only distorts market transaction prices and hinders resource allocation but also initiates adverse selection transactions, increasing liquidity risks and potentially precipitating market crashes, thereby impeding the market's healthy development. Utilizing information asymmetry theory and principal-agent theory, this paper analyzes data from A-share listed companies from 2011 to 2022. Employing a fixed-effect model, it empirically examines the influence of enterprise digital transformation on the likelihood of informed trading. The findings demonstrate that enterprise digital transformation markedly reduces the likelihood of informed trading. Further analysis of heterogeneity indicates that, compared to state-owned, non-high-tech enterprises and enterprises in the western region, the inhibitory effect on informed trading is more pronounced in non-state-owned, high-tech enterprises and enterprises in the eastern and central regions. Additionally, the chain mediation effect underscores that digital transformation weakens information asymmetry and strengthens internal controls, thereby reducing informed trading. Finally, employing a dynamic panel threshold model we find that digital transformation can only significantly inhibit the informed transactions when enterprises have reached a certain level of technological and asset accumulation.